2022
DOI: 10.3390/children9030365
|View full text |Cite
|
Sign up to set email alerts
|

Orthorexia Nervosa in Adolescents and Young Adults: A Literature Review

Abstract: Adolescents are a nutritionally vulnerable population; eating disorders are more common among adolescents and young adults. Orthorexia nervosa (ON) is a non-formally recognized condition characterized by an obsessive preoccupation with eating healthy and “pure” foods; the quality and not the quantity of food is pivotal in ON. ON is a complex entity which can be associated with severe diet restrictions, a negative impact on social relationships, and with physical and mental health conditions, including obsessiv… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1
1

Citation Types

1
14
0

Year Published

2022
2022
2024
2024

Publication Types

Select...
8
1

Relationship

1
8

Authors

Journals

citations
Cited by 18 publications
(15 citation statements)
references
References 84 publications
1
14
0
Order By: Relevance
“…Orthorexia nervosa is an informally diagnosed condition characterized by an obsessive preoccupation with eating healthy and “clean” food. In this condition, it is the quality, not the quantity, of food that is crucial [ 10 , 11 ]. Orthorexia nervosa, sometimes called radical eating, is a condition in which a pathological obsession with eating the “right” food is manifested.…”
Section: Introductionmentioning
confidence: 99%
See 1 more Smart Citation
“…Orthorexia nervosa is an informally diagnosed condition characterized by an obsessive preoccupation with eating healthy and “clean” food. In this condition, it is the quality, not the quantity, of food that is crucial [ 10 , 11 ]. Orthorexia nervosa, sometimes called radical eating, is a condition in which a pathological obsession with eating the “right” food is manifested.…”
Section: Introductionmentioning
confidence: 99%
“…Such behavior stems from the conviction that only eating healthy, easily digestible food and strict adherence to a diet will allow them to prevent the occurrence of diseases characteristic of modern societies-chronic non-communicable diseases [ 12 ]. Therefore, the desire to live a healthy and long life, to stay healthy and fit, and to focus on the quality of the food consumed rather than the quantity of the food consumed makes this disease not easy to diagnose [ 10 , 17 ]. There are also cases where patients who eliminate more products start consuming only water while believing that only drinking strictly selected water will ensure full health [ 5 ].…”
Section: Introductionmentioning
confidence: 99%
“…It is challenging to include ON between the OSFEDs or the obsessive–compulsive spectrum disorders because there are no unanimously accepted diagnostic criteria or sound epidemiological data ( 31 ). An online survey ( N = 343 Italian healthcare professionals) showed that ON is considered a variant of ED by most responders, while others classified this pathology as a prodromal phase or a stage in the evolution of anorexia nervosa (AN) ( 32 ).…”
Section: Other Eating Disorders-general Characteristicsmentioning
confidence: 99%
“…Orthorexia nervosa is another physical symptom of OCD (Gkiouleka et al, 2022). This has been defined as an obsessive preoccupation with eating healthy and "pure" foods or as a type of "healthism" which has been defined as thriving for the best possible eating and exercise behaviors.…”
Section: Orthorexia Nervosamentioning
confidence: 99%